Os agravos de trabalho sob o olhar da Política Nacional de Saúde do trabalhador (a) para a 12º Coordenadoria Regional de Saúde do Rs - Zwan, Sinara Danieli (2018)
This research compares the occurrence profile of work injuries, before and after the National Policy of Worker’s Health, in the 12nd Regional Health Coordination in Rio Grande do Sul, from 2008 to 2016. This study was exploratory, descriptive, transversal and also, a quantitative approach. It was used data from the Individual Reporting of Harm Notification (RINA) digital database, of State Information System. The data were analyzed in periods “before” and “after” PNSTT/2012 for the 24 cities belonging to 12nd CRS/RS. Initially, the descriptive analysis approached sociodemographic, occupational and work-related variables, following by the Chi-Square test, prevalence calculation. The results of the descriptive analysis indicated that harm to workers' health decreased after implementation of PNSTT. In the 12nd CRS/RS, the municipalities with the highest prevalence coefficient are Sete de Setembro, Mato Queimado and Vitória das Missões. São Borja has the lowest prevalence coefficient. Male workers aged 25-44 years and with less than 11 years of schooling are more likely to suffer from work-related harm. Considering occupational variables, the most reported type of injury was the typical accident. Although, the commuting accident and the occupational diseases denoted greater underreporting. Non-CLT employees are at greater risk of suffering harm, as well as, the CNAE Services. The most notificated injuries were caused by “contact”, and the most common injury types were in wrist and hand. The test indicated that the type of harm has an association with gender, level of education, type of employment relationship and age group. The probability of occurrence of work injuries was two times higher in males and in agriculture. In the CNAE Services, women present almost two times more chance of suffering from injuries compared to men, since women are influenced by urbanization rates in the research region and by uneven working conditions. SIST has proven to be a valuable tool for formulating an epidemiological database, listing responsible factors for the occurrence of injuries, and drawing regional profiles of them to promote prevention policies in workers’ health from RS. PNSTT seems to corroborate to the reduction in work-related injuries from 52% before PNSTT to 36% after PNSTT. Although, many difficulties in worker’s health have to be faced, mainly in the application of PNSTT guidelines and management problems considering the implementation of effective actions. In order to apply a policy, collective actions and the involvement of all social actors, such as workers, employers and society in general, are necessary in favor of a socially active, conscious and healthy working class construction.